ANALISIS RASIO LIKUIDITAS BERBASIS ARUS KAS PADA PT. MENARA PHINISI HOTELINDO KOTA MAKASSAR - Rizal, Samsul; Musdalifah, Musdalifah (Perpustakaan dan Penerbitan Unismuh Makassar, 2016)
Musadlipah. B, the analysis of cash flow-based liquidity ratio at PT. Phinisi Tower Hotelindo Makassar city, a thesis of faculty management program of economics and business of university muhammadiyah mentor I IdhamKhalik and mentor II Sri Andayaningsih.The purpose of this study is to determine the effect of liquidity and profit on earnings management is related to cash flow from operatioans and accruals. This study encloses financial statements. Then this research use liquidity ratio formula that is current ratio, quick ratio, and cash ratio then cash flow that is activity of operation, activity of invenstasi, and fund activity. It is expected that liquidity profit can predict future cash flow. The results of this study is that there is a significant to cash flow, this shows the ability of the company to pay current liabilies unaffected cash flow. On the contrary, cash flow affects a firm’s ability to pay its current liabilities.